MELANVEER : TEKNOLOGI PENDETEKSI PEMBULUH DARAH VENA UNTUK MENINGKATKAN PELAYANAN KESEHATAN) - Adeline, Ivone; Maulana, Andri; Hartriningsih, Salzabila; Adi Prasetyanto, Wisnu (Journal of Indonesian Medical Laboratory and Science, 2025)
Background: Intravenous (IV) procedures face challenges due to low nurse proficiency (50.8%) in Indonesian and difficulties in vein visualization, especially in patients with darker skin tones. Objectives: To develop an affordable, portable vein detection device, "Melanveer," capable of accurate visualization for all skin types. Materials and Methods: Melanveer uses near-infrared (NIR) light and Contrast Limited Adaptive Histogram Equalization (CLAHE) for real-time vein visualization. The prototype, made with 3D-printed components, was tested on 20 patients with varying skin tones (Very white to light white skin, Fair to light brown skin, and Dark to very dark brown skin). Results: Melanveer demonstrated 94% accuracy in vein detection, improved efficiency for medical staff, and enhanced patient comfort during IV procedures. Conclusions: Melanveer offers an innovative, cost-effective, and portable solution for accurate vein detection, addressing challenges in IV procedures and improving healthcare outcomes